Determinants of the Financial Performance of MSMEs Assisted by the Rakyat Sejahtera Abadi Credit Union Cooperative in Bekasi City: The Influence of Financial Literacy, Cooperative Capital Facilitation, and Fintech Adoption Moderated by Regulatory Support - Agtovia Frimayasa; Ibnu Haris Nasution (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a major pillar of Indonesia's economy; however, many cooperative-assisted MSMEs continue to experience difficulties in achieving sustainable financial performance due to limited financial capability, restricted access to capital, and uneven adoption of digital financial technologies. Despite the strategic role of cooperatives in supporting MSME development, empirical evidence integrating financial literacy, cooperative capital facilitation, fintech adoption, and institutional support within a single analytical framework remains limited. This study aims to examine the effects of financial literacy, cooperative capital facilitation, and fintech adoption on the financial performance of MSMEs assisted by the Rakyat Sejahtera Abadi Credit Union Cooperative in Bekasi City. Furthermore, it investigates the moderating role of regulatory support in strengthening these relationships. A quantitative explanatory approach was employed using survey data collected from 138 MSME owners. Data were analyzed using multiple regression and Moderated Regression Analysis (MRA) with SPSS. The results indicate that financial literacy, cooperative capital facilitation, and fintech adoption positively and significantly influence MSME financial performance, with fintech adoption emerging as the strongest predictor. Regulatory support also significantly strengthens the effects of all three determinants on financial performance, highlighting the importance of a supportive institutional environment in enhancing the effectiveness of financial capability, cooperative financing, and digital technology adoption. This study contributes to the MSME literature by integrating financial, technological, and institutional perspectives into a comprehensive analytical framework, while providing practical implications for policymakers, cooperatives, and MSME owners in designing more effective strategies to improve business sustainability and competitiveness.